TECHNIQUE TO RECORD NEUTRAL ZONE IN SEVERELY RESORBED MANDIBULAR RIDGE IN COMPLETELY EDENTULOUS PATIENT – A CASE REPORT. (CAHIERS MAGELLANES-NS, 2024)
Primary objectives of complete denture therapy include placement of a structural, functional and esthetic dentition substitute, with adequate replacement of supporting structures. Fabrication of a denture with facio-lingual ill suited positioning of denture teeth or physiologically unacceptable denture base shape have been incriminated in poor prosthesis stability and retention,1,2,3 disturbed phoneics,4,5 inadequate facial tissue support,5,6 and hyperactive gagging.7Rehabilitation of patients with severly resorbed ridges poses a challenge for the dentist . various techniques and materials have been employed to provide a patient with a stable and functional dentures. Neutral zone is that area or zone where all the forces created by the tongue and cheeks or lips are nullified There are various terminologies that have been associated with this concept, including zone of minimal conﬂict ,dead zone, stable zone, zone of equilibrium, biometric denture space and potential denture space.8,9 This technique is most effective for patients who have severely resorbed mandibular ridge and there is difficulty in positioning the teeth to produce a stable mandibular denture.10 The purpose of this case report is to present the use of the neutral zone technique for the fabrication of successful and stable mandibular complete denture to rehabilitate a patient with severely resorbed ridges. The neutral zone technique can be incorporated to provide the patient with a stable and functional denture..